Gambaran Perkembangan Motorik Kasar pada Balita Usia 1-3 Tahun dengan Stunting di Wilayah Kerja Puskesmas Sumberjambe, Jember - Nadia Farah Meidina; Lantin Sulistyorini; Peni Perdani Juliningrum (UPT Percetakan dan Penerbitan Universitas Jember, 2019)
The condition of stunting toddlers can affect the ability in aspects of gross motor development. Gross motor development of stunting toddlers is also influenced by optimal nutritional status between the balance of intake and nutritional needs. This study aims to determine the description of gross motor development in stunted infants aged 1-3 years (toddler) in Sumberjambe Health Center, Jember Regency. This study used a descriptive design with a cross sectional approach. Respondents within this study were 200 stunted toddlers with purposive sampling method. The data collection was carried out using the Denver II observation sheet. Data analysis was performed by descriptive analysis by describing data in table form. The results of gross motor development found that 144 infants (72,0%) had normal gross motor development, 43 toddlers (21,5%) had suspected, and 13 toddlers (6,5%) had abnormal gross motor development. The role of parents, family, and the environment is expected to be able to be involved and directly control the condition of toddlers by frequently interacting to determine motor skills in achieving gross motoric development that is optimal in stunted toddlers.